BRS Expedito: a new black-seeded common bean cultivar - Antunes, Irajá Ferreira; Silveira, Expedito Paulo; Silva, Heloisa Torres da (Pesquisa Agropecuaria Brasileira, 2007)
BRS Expedito, obtained from the cross of CNF 5491 x FT Tarumã, is a black-seeded common bean, with a mean growth cycle of 88 days, and is a cultivar recommended for cultivation in Rio Grande do Sul State, Brazil. Its mean seed yield from 1997/1998 to 2004/2005 reached 2,359 kg ha-1, which was 11.18% above control means, and it presented resistance to anthracnose. Mean 100-seed weight was 28.2 g, and protein content was 29%, the highest value observed among cultivars realeased in the State. Its crude fiber content is similar to those of top cultivars. It presents indeterminate growth habit, plant architecture type II and good lodging resistance, being suitable to mechanical harvest.